Chapter Massimo Quaini, studioso del paesaggio - MARSON, ANNA (Territori, 2021)
Landscape represents, for Massimo Quaini's research activities and publications, a recurrent and growing focus: from early 70's studies about rural landscapes of Liguria, to Hérodote/Italia, to later writings directly inquiring this concept and relating its fortune to 'modernity crisis', calling for grassroots action in order to reactivate local practices and knowledge, essential for developing landscape potentialities as a political project. This essay reflects upon publications and research experiences which contribute to define the specific legacy of Quaini as a landscape scholar, outlining a unique figure in the Italian context.